Theory of Planned Behavior Implementation on the Factors Affecting Self-Care Management in Type 2 Diabetes Mellitus Patients - Ana Damayanti; Didik Tamtomo; Dono Indarto (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Diabetes mellitus (DM) is one of the largest global health emergencies in the 21st century. Diabetes self-management education (DSME) is a continuous process of knowledge transfer in order to improve skill and ability of diabetic patient to perform self-care management, which reduces blood glucose level and prevent diabetic complications. The success of DSME is determined by behavior changes of diabetic patients, which can be assessed using behavior theories including Theory of Planned Behavior (TPB). This study aimed to analyze the factors affecting self-care management in patients with type 2 DM using TPB.Subjects and Method: A randomized controlled trial study was carried out in 7 community health centers in Tarakan City, North Kalimantan, from March to May, 2018. A sample of 126 type 2 DM patients was selected by simple random sampling. The dependent variable was self-care management. The independent variables were intention, attitude, subjective norm, self-efficacy, and education level. The data was collected by questionnaire and analyzed by path analysis.Results: Self-care management was positively and directly affected by education ?senior high school (b= 7.10; SE= 3.22; p= 0.028) and strong intention (b= 2.40; SE= 0.75; p= 0.001). Self-care management was indirectly affected by self-efficacy, attitude, and subjective norm trough intention.Conclusion: Self-care management in type 2 DM is directly affected by education and strong intention. These findings support the TPB implementation in self-care management.Keywords: self- care management, type 2 DM, Theory of Planned BehaviorCorrespondence: